A charaterization of closed maps using the whyburn construction - Yvonne O. Stallings (International Journal of Mathematics and Mathematical Sciences)
In this paper we modify the Whyburn construction for a continuous function f:X→Y. If the range is first countable, we get a characterization of closed maps; namely, the constructions are the same if and only if the map is closed.